EFFICACY OF RECTAL MISOPROSTOL VS INTRAVENOUS OXYTOCIN IN PREVENTING POSTPARTUM HEMORRHAGE FOLLOWING ELECTIVE CAESAREAN SECTION - Shah, Mehtab; Urooj, Heera; Shazma Shah; Rahim, Rehana (Journal of Postgraduate Medical Institute, 2021)
Objective: To compare the efficacy of rectal misoprostol with intravenous oxytocin in prevention of postpartum hemorrhage (PPH) in elective cesarean section (CS) operation. Methodology: This randomized controlled trial was conducted in the Department of Obstetrics & Gynecology Department, Lady Reading Hospital, Peshawar. A total of 334 women undergoing elective CS were recruited in the study through consecutive sampling and randomly allocated to misoprostol group (group A) and IV oxytocin group (Group B). Follow up was done to determine the mean blood loss in both groups to determine the efficacy in terms of presence or absence of postpartum hemorrhage. Results: The mean age in group A was 31.2±6.8 years compared to 30±6.2 years in group B. The mean blood loss in group A was 776±285.7 ml, while in group B it was 817±1318 ml. Efficacy of rectal misoprostol was 83.8% as compared to 74.9% for I/V Oxytocin with a significant p-value of 0.043. Conclusion: Rectal misoprostol in women prepared for elective cesarean section show better efficacy in terms of PPH prevention as compared to IV oxytocin.